2016
DOI: 10.1103/physrevb.94.014422
|View full text |Cite
|
Sign up to set email alerts
|

EuCo2P2: A model molecular-field helical Heisenberg antiferromagnet

Abstract: The metallic compound EuCo2P2 with the body-centered tetragonal ThCr2Si2 structure containing Eu spins-7/2 was previously shown from single-crystal neutron diffraction measurements to exhibit a helical antiferromagnetic (AFM) structure below TN = 66.5 K with the helix axis along the c axis and with the ordered moments aligned within the ab plane. Here we report crystallography, electrical resistivity, heat capacity, magnetization and magnetic susceptibility measurements on single crystals of this compound. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 51 publications
12
49
1
Order By: Relevance
“…Within MFT, this turn angle indicates dominant AFM nearest-layer and also next-nearest-layer Eu-Eu interactions [42,43]. Similar incommensurate Eu helical spin structures along the c axis with almost the same propagation vector were found in the isostructural compounds EuCo 2 P 2 and EuCo 2 As 2 [17,19,21,22].…”
Section: A Magnetic Susceptibility Measurementssupporting
confidence: 60%
See 1 more Smart Citation
“…Within MFT, this turn angle indicates dominant AFM nearest-layer and also next-nearest-layer Eu-Eu interactions [42,43]. Similar incommensurate Eu helical spin structures along the c axis with almost the same propagation vector were found in the isostructural compounds EuCo 2 P 2 and EuCo 2 As 2 [17,19,21,22].…”
Section: A Magnetic Susceptibility Measurementssupporting
confidence: 60%
“…High-pressure studies on EuCo 2 P 2 showed that the system changes its magnetic character from Eu(4f )-sublattice ordering to Co(3d)-sublattice ordering coincident with a pressure-induced first-order ucT to collapsed tetragonal (cT) structural transition [18]. We recently showed that EuCo 2 P 2 at ambient pressure is a textbook example of a noncollinear helical AFM for which the thermodynamic properties in the AFM state are well described by our so-called unified molecular field theory (MFT) [19]. Similarly, single crystals of EuCo 2 As 2 , which is isostructural and isoelectronic to EuCo 2 P 2 , exhibit coplanar helical AFM ordering of Eu +2 spins below 47 K but with anomalously-enhanced effective and/or ordered moments [8,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The χ ab (T ) data for x = 0.40 and 0.45 in Fig. 1, which remain relatively large with respect to χ c (T ) at T ≪ T N , suggest that the AFM structure in this x range is either extrinsically or intrinsically noncollinear [37][38][39]. In either case, the high-field M ab (H) behavior is not straightforward to interpret.…”
mentioning
confidence: 72%
“…In classical molecular-field theory 32 , the parameter f ≡ T θ /T c is usually found to be smaller than 1 with −∞ < f < −1 for antiferromagnets and 1 for ferromagnets. This is because the real transition (either FM or AF) has to arise before the divergence of χ(q) which describes the instability of the system towards a particular magnetic state.…”
Section: A Magnetization and Magnetic Susceptibility Datamentioning
confidence: 99%